Identification and expression analysis of toll-like receptor genes (TLR8 and TLR9) in mucosal tissues of turbot (Scophthalmus maximus L.) following bacterial challenge. (November 2016) - Dong, Xiaoyu; Su, Baofeng; Zhou, Shun; Shang, Mei; Yan, Hao; Liu, Fengqiao; Gao, Chengbin; Tan, Fenghua; Li, Chao
Abstract: Mucosal immune system is one of the most important components in the innate immunity and constitutes the front line of host defense against infection, especially for teleost, which are living in the pathogen-rich aquatic environment. The pathogen recognition receptors (PRRs), which can recognize the conserved pathogen-associated molecular patterns (PAMPs) of bacteria, are considered as one of the most important component for pathogen recognition and immune signaling pathways activation in mucosal immunity. In this regard, we sought to identify TLR8 and TLR9 in turbot ( Scophthalmus maximus ), as well as their mucosal expression patterns following different bacterial infection in mucosal tissues for the first time. The full-length TLR8 transcript consists of an open reading frame (ORF) of 3108 bp encoding the putative peptide of 1035 amino acids. While the TLR9 was 6730 bp long, containing a 3168 bp ORF that encodes 1055 amino acids. The phylogenetic analysis revealed both TLR8 and TLR9 showed the closest relationship to large yellow croaker. Moreover, both TLR8 and TLR9 could be detected in all examined healthy turbot tissues, with the lowest expression level in liver and a relatively moderate expression pattern in healthy mucosal tissues. Distinct expression patterns of TLR8 and TLR9 were comparatively observed in the mucosal tissues (intestine, gill and skin) following Vibrio anguillarum and Streptococcus iniae infection, suggesting their different roles for mucosal immunity. Further functional studies are needed to better characterize TLR8 and TLR9 and their family members, to better understand the ligand specificity and to identify their roles in different mucosal tissues in protecting fish from the pathogenically hostile environment. Highlights: TLR8 and TLR9 were identified in turbot. TLR8 and TLR9 were ubiquitously expressed in turbot tissues. TLR8 and TLR9 were significantly induced after bacterial challenge.